Evaluasi Produksi Maggot Black Soldier Fly (BSF) pada Media Ekskreta Puyuh Periode Layer: Evaluation of the Production of Black Soldier Fly (BSF) Maggots in Quail Excreta Media During the Layer Period - Ayuningtyas, Gilang; Alfiyyah Yasmin, Fairuz; Sembada, Pria; Priyambodo, Danang; Fit Rayani, Tera; Purwanto, Bagus Priyo; Awaliyah, Izatullah Rizky; Nurfitriani, Dini; Afgani, Nawangsari Aulya; Pangestu, Puguh; Khoirunnisa, Luthfi; Agustin, Adinda Dwina (Jurnal Agroekoteknologi dan Agribisnis, 2024)
The accumulation of ammonia in excreta waste cause air pollution and health problems for both humans and livestock. A solution to address this issue is through the bioconversion process using Black Soldier Fly larvae (BSFL). This study aims to evaluate the feasibility of Black Soldier Fly Larvae (BSFL) production using quail excreta as a growth medium and to analyze biomass production (BSFL and BSFL Frass) because of bioconversion. This study used a Randomized Block Design consisting of 2 treatments: non-fermented quail excreta (P0) and fermented quail excreta (P1). The bioconversion process was carried out at 3 different time periods. The variables observed are bioconversion indicators: growth rate, conversion efficiency (ECI), the weight of the BSFL, the weight and the characteristics of the BFSL frass. The data were analyzed using analysis of variance (ANOVA), followed by the Least Significant Difference (LSD) test. The average growth rate of BSFL P0 (10.97%) and P1 (12.52%) was not significantly different, in line with the conversion efficiency (ECI) value in the P0 treatment (0.08) and P1 treatment (0.11). The bioconversion results showed that the production of BSFL in non-fermented quail excreta media reached 10.97% ± 6.74%, while in fermented excreta media it reached 12.52% ± 1.98%. This study indicates that quail excreta have the potential as a medium for BSFL production, and the excreta fermentation process does not have a significant effect on the bioconversion process based on bioconversion indicator variables.